Human enzymes involved in the metabolic activation of carcinogenic aristolochic acids: evidence for reductive activation by cytochromes P450 1A1 and 1A2 - Stiborová, M; Frei, E; Wiessler, M; Schmeiser, H H (Chemical research in toxicology, 2001)
Aristolochic acid (AA), a naturally occurring nephrotoxin and rodent carcinogen, has recently been associated with the development of urothelial cancer in humans. Determining the capability of humans to metabolize AA and understanding, which human enzymes are involved in AA activation is important in the assessment of individual susceptibility. Using the nuclease P1-enhanced version of the (32)P-postlabeling assay, we compared the ability of human, minipig and rat hepatic microsomal samples to activate AA to metabolites forming DNA adducts. Human microsomes generated AA-DNA adduct profiles reproducing those found in renal tissues from humans exposed to AA. Identical patterns of AA-DNA adducts were also observed when AA was activated by minipig and rat microsomes. Therefore, microsomes of both animals are suitable in vitro systems mimicking the enzymatic activation of AA in humans. To define the role of specific P450 enzymes and NADPH:P450 reductase in the activation of AA by human microsomes we investigated the modulation of AA-DNA adduct formation by specific inducers or selective inhibitors of P450s and cofactors or inhibitors of NADPH:P450 reductase. The inducer of P450 1A1/2, beta-naphthoflavone, significantly stimulated the levels of AA-DNA adducts formed by rat microsomes, but inducers of P450 2B1/2 and 2E1 had no such effect. Furthermore, only inhibitors of the P450 1A subfamily (alpha-naphthoflavone, furafylline) significantly decreased the amount of adducts formed by microsomes from humans, minipigs and rats. alpha-Lipoic acid, an inhibitor of NADPH:P450 reductase, inhibited adduct formation too, but to a lower extent. On the basis of these results, we attribute most of the microsomal activation of AA to P450 1A1 and 1A2, although a role of NADPH:P450 reductase cannot be ruled out. With purified enzymes (recombinant P450 1A1/2 and NADPH:P450 reductase) and microsomes from baculovirus transfected insect cells expressing recombinant human P450 1A1/2 and NADPH:P450 reductase, the participation of these enzymes in the formation of AA-DNA adducts was confirmed. These results are the first report on the activation of AA by human enzymes and clearly demonstrate the role of P450 1A1, 1A2, and NADPH:P450 reductase in catalyzing the reductive activation of AA.
Keywords: Microsomes, Liver; Gene Expression Regulation; prasata; Cytochrome P-450 CYP1A2; Swine; adukty DNA; Male; Rats, Wistar; Cytochrome P-450 CYP1A1; cytochrom P-450 CYP1A1; mužské pohlaví; potkani Wistar; Aristolochic Acids; oxidace-redukce; krysa rodu Rattus; cytochrom P-450 CYP1A2; Phenanthrenes; kyseliny aristolochové; radioizotopy fosforu; Animals; lidé; Carcinogens; NADPH-Ferrihemoprotein Reductase; karcinogeny; Humans; zvířata; regulace genové exprese; DNA Adducts; Rats; Catalysis; Phosphorus Radioisotopes; NADPH-cytochrom c-reduktasa; Oxidation-Reduction; katalýza; jaterní mikrozomy; fenantreny